A Distributed Systems Architecture for the 1990's - Birrell, Andrew; Lampson, Butler; Schroeder, Mike (Digital Equipment Corp. Systems Research Center, 1989)
Most markets for computing are evolving towards distributed solutions. The system framework that accommodates distributed solutions most gracefully is likely to dominate in the 1990’s. A leadership distributed system includes the best of today’s centralized systems, combining their coherence and function with the better cost/performance, growth, scale, geographic extent, availability, and reliability possible in distributed systems. To build such a system requires a distributed systems architecture as the framework for a wide variety of products. The architecture specifies a set of standard services in a distributed system. Together these services make up an integrated system with global names, access, availability, security, and management, all working uniformly throughout the system. This report summarizes a complicated subject in only ten pages (not counting the appendix). We made it as short as we could. Please read it all.